Hesitation about coronavirus vaccines in healthcare professionals and general population in Spain - Francesc Saigí-Rubió; Hans Eguia; Albert Espelt; Salvador Macip; Marina Bosque-Prous (PLoS ONE, 2022)
Background This study attempts to provide a picture of the hesitancy to vaccination against COVID-19 in Spain during the 2021 spring-autumn vaccination campaign, both in the general population and in healthcare professionals. Methods The participants were recruited using social media such as Facebook and Twitter, in addition to the cooperation of health personnel contacted with the collaboration of medical scientific societies. A cross-sectional study was carried out that included the response of an online questionnaire. The data were collected from April 30 to September 26, 2021. To assess the different associations between variables to be measured, we fit Poisson regression models with robust variance. Results Responses were obtained from 3,850 adults from the general population group and 502 health professionals. Of the overall sample, 48.6% of participants from the general population were vaccinated against COVID-19, whereas in the healthcare professionals, 94.8% were vaccinated. The prevalence of general population vaccination increased with age, and was higher in women than men. Most participants did not show a preference for any vaccine itself. However, the prevalence of people vaccinated with their preferred vaccine was higher for the ones vaccinated with Pfizer’s vaccine. 6.5% of the general population reported being reticent to be vaccinated. People from younger age groups, people with lower educational levels and those who were not from a risk group showed greater reluctance to be vaccinated. No gender differences in reluctancy were found. Conclusions Health professionals were significantly less likely to refuse vaccination even though they had more doubts about the safety and efficacy of vaccines. On the other hand, younger people, those with a lower level of education and those who were not from a risk group were the most hesitant.